Search for a heavy narrow resonance decaying to $e μ$, $e τ$, or $μ τ$ with the ATLAS detector in $\sqrt{s}=7$ TeV $pp$ collisions at the LHC - ATLAS collaboration (2895 authors) (2013)
This letter presents the results of a search for a heavy particle decaying into an e mu, e tau, or mu tau final state in pp collisions at sqrt(s) = 7 TeV. The data were recorded with the ATLAS detector at the LHC during 2011 and correspond to an integrated luminosity of 4.6/fb. No significant excess above the Standard Model expectation is observed, and exclusions at 95% confidence level are placed on the cross section times branching ratio for the production of an R-parity-violating supersymmetric tau sneutrino. These results considerably extend constraints from Tevatron experiments.